Fiscal policy and capital flows: evidence for some countries in Latin America - Lozano Espitia, Luis Ignacio; Melo-Becerra, Ligia Alba; Ramos, Jorge Enrique (Universidad Pedagógica y Tecnológica de Colombia, 2016)
Capital flows represent opportunities to finance the growth and development of countries, but they also entail risks, including macroeconomic and financial. Policy responses to mitigate its effects play an important role especially in emerging markets. This paper evaluates the fiscal policy stance in front to shocks on capital flows recorded during the last two decades in six emerging economies of Latin America: Argentina, Brazil, Chile, Colombia, Mexico and Peru.Based on the characterization of the different episodes of sudden inflows and outflows of capital and on the results of a panel data model with instrumental variables, we found that governments did not responded with exceptional fiscal measures. By contrast, the procyclicality in the fiscal stance seems to be associated to the effect of capital flows on economic activity.